In vitro and in vivo Equivalence of Two Oral Atenolol Tablet Formulations - Cuadrado, Antonio; Gascón, Alicia Rodríguez; Hernández, Rosa María; Castilla, Ana María; Maza, Ane de la; Ocáriz, Alici López de; Calvo, Begoña; Pedraz, José Luis (Arzneimittelforschung, 2002)
A randomised, cross-over, open study of bioequivalence between two different atenolol (CAS 29122-68-7) tablet formulations is presented. An in vitro comparative study between the two formulations was also performed. Both products meet the USP 23 (United States Pharmacopea) specification. The values of similarity factor (f2) and difference factor (f1) obtained ensure sameness or equivalence of the two dissolution curves. Twenty-four healthy volunteers (male/female) participated in the bioequivalence study. Each treatment was given as a single 100-mg tablet following an overnight fast. Atenolol concentrations in plasma were determined up to 30 h after treatment by HPLC. The pharmacokinetic parameters AUC0–∞, Cmax and Cmax/AUC0–∞ were tested for bioequivalence after logarithmic transformation of data and ratios of tmax were evaluated nonparametrically. The parametric analysis revealed the following test/reference ratios and their 90 % confidence intervals (90 % CI): 1.06 (0.99−1.13) for AUC, 1.07 (0.97−1.18) for Cmax, and 0.99 (0.94−1.07) for Cmax/AUC0–∞. The 90 % CI for tmax was 0.91−1.23. All parameters showed bioequivalence between both formulations. A discrete fallin both systolic (SBP) and diastolic (DBP) blood pressure was observed after the drug administration. The fall extent (approximately 11 mmHg in supine position) and the time course of both parameters after the drug administration was similar for both formulations. Minimal values for SBP and DBP were achieved at 6 h after the drug administration for both formulations. Heart rates were also reduced after the administration of both formulations of atenolol in a similar extent (12 b.p.m.) and following a similar time profile (i.e. maximal reductions were observed between 1 and 3 h after the drug administration). It can be concluded that both formulations are equivalent in vitro and in vivo.
Keywords: Atenolol, bioavailability, bioequivalence, pharmacokinetics; Atenolol CINFA®; CAS 29122-68-7